Analysis of Excavator Productivity in Bore Pile Foundation Drilling Using the 5W + 1H Method - Joel M Simanullang; Agus Nugroho (Potensi: Jurnal Sipil Politeknik, 2025)
The increasing traffic congestion has driven the development of the Solo–Yogyakarta–Yogyakarta International Airport toll road project, which involves drilling bore piles using heavy excavators. This study aims to evaluate excavator productivity by analyzing the percentage of value-added activities (VAA) and non-value-added activities (NVAA), using the Manufacturing Cycle Effectiveness (MCE) method combined with the 5W + 1H approach. The novelty of this research lies in integrating MCE and the 5W + 1H framework for analyzing construction equipment, providing a structured framework to identify the root causes of productivity losses beyond conventional time–motion studies. The results from three case samples reveal that NVAA dominates VAA, with idle time being the primary factor that reduces productivity. These findings underscore the importance of enhancing interteam coordination, optimizing work sequencing, and minimizing standby periods to improve excavator efficiency in bore pile operations. Practically, the proposed analysis provides construction managers with actionable insights to minimize inefficiencies, reduce project costs, and improve scheduling reliability. However, the study is limited by its focus on a single project location and three observation samples, which may restrict generalizability. Future research should extend the method to larger datasets and diverse project settings to strengthen its applicability